IMPLEMENTASI RAD DALAM PENGEMBANGAN APLIKASI PENJUALAN KEBAB BERBASIS ANDROID - Maulana Hakim, Muh Arif; Dasa Putri, Anggia (Computer Science and Industrial Engineering, 2025)
In this digital era, technological advancements have transformed many manual activities into digital ones, making them easier to manage. One of these is in the field of buying and selling products, where before the existence of digitalization, product sales still used conventional methods, especially in recording transactions. The method of recording transactions using transaction notebooks often suffers from damage and human errors in recording transactions and consumes costs and effort. With the advent of digitalization, developing an Android-based sales application using the Rapid Application Development (RAD) method allows us to quickly build Android-based applications using the Flutter framework and design the system using Unified Modeling Language (UML) to get an overview of the system being created. By using the Android-based sales application with the Rapid Application Development (RAD) method we can understand the speed and efficiency of designing applications, and through digital-based applications, we can increase sales and reduce human errors and various unwanted incidents.